2016
DOI: 10.1007/s12098-015-1956-3
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome Evaluation System (SES) versus Blood Culture (BACTEC) in the Diagnosis and Management of Neonatal Sepsis - A Randomized Controlled Trial

Abstract: This new molecular based diagnostic system (SES) helps in rapid and accurate diagnosis of neonatal sepsis and reduces mortality and morbidity in affected neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This study also demonstrates the relatively low sensitivity of blood cultures for detecting bacteraemia in this age group. Other studies hold promise for advanced polymerase chain reaction‐based methods that may be more sensitive than current methods .…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrates the relatively low sensitivity of blood cultures for detecting bacteraemia in this age group. Other studies hold promise for advanced polymerase chain reaction‐based methods that may be more sensitive than current methods .…”
Section: Discussionmentioning
confidence: 99%
“…In 2 randomized intervention studies by Tafelski et al and Bhat et al, there were significantly fewer adjustments made when using SeptiFast (13.5% vs 9.8%) [ 20 , 21 ] and another intervention study by Cambau et al found a significant increase in the use of appropriate antimicrobials (23.6% vs 33.6%) [ 22 ]. In prospective studies by Mancini et al and Tschiedel et al, the use of SeptiFast resulted in higher rates of antibiotic changes [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The laboratory strives to provide rapid pathogen identification, with which providers can optimize antimicrobial utilization and improve patient outcomes. The use of rapid diagnostics performed on positive blood culture broths revealed the effect on sepsis mortality and operational outcomes for adult and pediatric patients with bacteremia or fungemia (2,3,15,(17)(18)(19)(20)(21). In other studies, only operations and costs of care were assessed (13,22).…”
Section: Clinical Microbiology Laboratory's Role In Value-based Care mentioning
confidence: 99%
“…In cases of sepsis, rapid intervention with appropriate antimicrobial therapy can be critical to patient survival (30)(31)(32). In reports describing mortality for bloodstream infection caused by aerobes, anaerobes, and fungi, appropriate antibiotic therapy increases survival by over 25% (2,3,15,(17)(18)(19)(20)(21)18). Eliminating delays in appropriate antibiotic administration is said to increase survival by approximately 7%-10% per hour (33).…”
Section: Mini-reviewsmentioning
confidence: 99%